A Roadmap for Tracking Knowledge Results – Experiences and Challenges - Walsh, Christopher; Simon, Yehude; Silverman, Sheryl; Sultan, Sara (World Bank, Washington, DC, 2012)
From fostering expertise to packaging and sharing lessons from the field, the knowledge work of the World Bank Group takes many shapes. But unlike lending operations, knowledge work is not always subject to the same results monitoring processes. For example, the publishing of a report has often been used as the only indicator of a successful knowledge product. During a program-wide effort to develop and implement a results-based management framework for its technical assistance work, the Water and Sanitation Program (WSP), a multi-donor partnership administered by the World Bank, discovered that applying the same framework to its knowledge work helped demonstrate the value of knowledge by drawing a connection between knowledge inputs, outputs, outcomes, and impact. This smart lesson describes lessons from a technical assistance program's experience applying a results framework to knowledge work. In addition to demonstrating value, this helped better define different stages of knowledge work, measure progress, and better manage program communications and knowledge management.